Peran Penyidik Dalam Mengungkapkan Kasus Pembunuhan Dan Pelaku Yang Menghilangkan Barang Bukti - Siti Nur Haliza; Zainudin Hasan; Shefa Rindya Yazhalina; Mela Yasa (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
In the current situation, the increase in murder cases is of great concern, especially with the development of technology, it also affects the ease of disseminating information which is then misused to track the location of the victim and suppress the victim with threats - threats that are not good related to the victim's purpose, namely to find out how the role of investigators to uncover murder cases that lose evidence and to find out the inhibiting factors of police investigators in carrying out the investigation process against the crime of murder. The research method used is normative legal research. The legal materials used are sourced from the literature. The types of legal materials used are primary, secondary, and tertiary legal materials. The technique of collecting legal materials is by document study. Analysis of legal materials using interpretation or interpretation. The results of the study indicate that the Criminal Acts of Murder and Removing Goods have been regulated in Article 338 of the Criminal Code that anyone who deliberately takes the life of another person, shall be punished for murder with a maximum imprisonment of 15 years, and Article 221 paragraph 1 number 2 of the Criminal Code, anyone who commits an act of covering up the criminal act committed, by destroying, removing and hiding evidence and evidence shall be punished with a maximum imprisonment of four years.